Episodic memory and beyond The hippocampus and neocortex in transformation. [article]. - Moscovitch, Morris
The last decade has seen dramatic technological and conceptual changes in research on episodic memory and the brain. New technologies, and increased use of more naturalistic observations, have enabled investigators to delve deeply into the structures that mediate episodic memory, particularly the hippocampus, and to track functional and structural interactions among brain regions that support it. Conceptually, episodic memory is increasingly being viewed as subject to lifelong transformations that are reflected in the neural substrates that mediate it. In keeping with this dynamic perspective, research on episodic memory (and the hippocampus) has infiltrated domains, from perception to language and from empathy to problem solving, that were once considered outside its boundaries. using the component process model as a framework, and focusing on the hippocampus, its subfields, and specialization along its longitudinal axis, along with its interaction with other brain regions, we consider these new developments and their implications for the organization of episodic memory and its contribution functions in other domains. -- (from the authors)
Keywords: Cebeza, Roberto; Winocour, Gordon; Nadel, Lynn; Episodic memory; Frontal cortex; Hippocampus; Parietal cortex; Schema; Transformation